2023
DOI: 10.2169/internalmedicine.0343-22
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Diffuse Bilateral Minute Pulmonary Meningothelial-like Nodules Increasing over the Short Term and Resembling Metastatic Lung Cancer

Abstract: A 54-year-old woman was referred to our hospital because computed tomography (CT) revealed multiple lung nodules during a health checkup. The nodules were up to 5 mm in diameter and randomly distributed in both lungs, appearing ring-shaped. No clinical symptoms were present. However, the nodes proliferated, and multiple lung metastases could not be ruled out, so a biopsy was performed to establish a diagnosis. She was diagnosed with minute pulmonary meningothelial-like nodules (MPMNs), and her condition had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Pulmonary minute meningothelial-like nodules (MMNs) are tiny nests of spindledto-epithelioid cells generally centered on small pulmonary veins, representing common incidental findings acquired during life in the lung, although their functional significance is still uncertain [1][2][3][4][5][6]. The incidence of multiple MMNs in pulmonary resections ranges from 1.1% to 9.5% [5,6,36]. Some authors have suggested that MMNs may be present in all abnormal lungs with chronic lung disease if sufficiently sampled, particularly in women in their sixth decade of life, in whom hormonal stimulation and chronic lung diseases with hypoxemic conditions possibly induce the growth of interstitial meningothelial cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary minute meningothelial-like nodules (MMNs) are tiny nests of spindledto-epithelioid cells generally centered on small pulmonary veins, representing common incidental findings acquired during life in the lung, although their functional significance is still uncertain [1][2][3][4][5][6]. The incidence of multiple MMNs in pulmonary resections ranges from 1.1% to 9.5% [5,6,36]. Some authors have suggested that MMNs may be present in all abnormal lungs with chronic lung disease if sufficiently sampled, particularly in women in their sixth decade of life, in whom hormonal stimulation and chronic lung diseases with hypoxemic conditions possibly induce the growth of interstitial meningothelial cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports of an increase in the number of MPMN in multiple lesions over time. Although rare, Murata et al 6 reported an increase in the number of diffuse GGN at 4 months, which were difficult to distinguish from metastatic lung tumours on CT imaging.…”
Section: Discussionmentioning
confidence: 99%